Dynamics of personal development on healthy students - Kramida, I.E. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2013)
The aim is to study the effectiveness of different physical training for the relatively healthy students. The study involved 1004 students. The directions of development of the students’ positive personal qualities. Found that the positive development of personality of students observed mostly on the first and third year than in the second. Could not find significant differences between the growth estimates of development of personality traits of students in classes in the sample program and the program specializations. Found that the rate of development of students’ personality traits minor: the average growth estimates for core positive personal qualities for 3 years does not exceed 10% of the maximum possible level. Recommended in the classroom more emphasis on developing positive personality traits. It is shown that special attention should be paid to the development of emotional stability of students and their tolerance towards other people.